On point for the military [integrated fighting ensemble combat outfit]. - Kumagai, J.
The US Army is in the midst of a transformation. In this paper, the author examine who defines the technology that is going to make this happen. The paper details how the aim is to create an integrated fighting ensemble combat outfit, which carries with it everything that a soldier will need
Keywords: Integrated fighting ensemble combat outfit; Military technology